Metrology test object for dimensional verification in additive manufacturing of metals for biomedical applications. (January 2015) - Teeter, Matthew G; Kopacz, Alexander J; Nikolov, Hristo N; Holdsworth, David W
Additive manufacturing continues to increase in popularity and is being used in applications such as biomaterial ingrowth that requires sub-millimeter dimensional accuracy. The purpose of this study was to design a metrology test object for determining the capabilities of additive manufacturing systems to produce common objects, with a focus on those relevant to medical applications. The test object was designed with a variety of features of varying dimensions, including holes, cylinders, rectangles, gaps, and lattices. The object was built using selective laser melting, and the produced dimensions were compared to the target dimensions. Location of the test objects on the build plate did not affect dimensions. Features with dimensions less than 0.300 mm did not build or were overbuilt to a minimum of 0.300 mm. The mean difference between target and measured dimensions was less than 0.100 mm in all cases. The test object is applicable to multiple systems and materials, tests the effect of location on the build, uses a minimum of material, and can be measured with a variety of efficient metrology tools (including measuring microscopes and micro-CT). Investigators can use this test object to determine the limits of systems and adjust build parameters to achieve maximum accuracy.